Post Delivery And Service Follow Up Process Model In Toyota Auto 2000 Sukun, Malang - Anna Triwijayati; Grace Herliana (Cita konsultindo, 2024)
This research aims to develop a model and survey instrument for after-repair service customer satisfaction at Auto2000 Sukun, Malang City. The research objective is based on follow-up case observations during after sales and after service at the Auto2000 Sukun dealer and repair company, in Malang City. In the follow-up workflow, the company still applies a semi-manual process, so the input error rate is very large. In addition, the survey instrument was applied separately to the two follow-up pathways. This type of research is case study research and is applicable/action research in a company. The focus of the case study in this research is on customer satisfaction follow-up, namely Post Delivery and Service Follow Up (PDSFU). The research was carried out at the Mechanic and Customer Relationship Coordinator (CRC) Service Unit. Researchers were involved as full participants in designing follow-up models and instruments. The research results show that the follow-up process can be more efficient and effective by designing an automated follow-up and survey system. Through system automation, data will be processed in more detail, with minimal errors and easier data processing. A reliable follow-up survey system will provide benefits in terms of accuracy and useful data information for the company